(3GdOQQ GdcGefI aj CYjGf GdeGFI GdKGefIs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3JQLeg (B: (3Ydi Hf EHQGgje Hf CSO GdeUQi s
(3BNQgG (B:s
(3JQLeI (B: (3jhSa Hf eMeO GdZSi s
(3GdfUa GdKGfis
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B147 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs